Prevalence of hypertension in endemic and non-endemic areas of Keshan disease: A cross-sectional study in rural areas of China - Hou, Jie; Zhu, Lifang; Jin, Shuran; Li, Jinshu; Xing, Zhifeng; Wang, Yanling; Wan, Xiaoyan; Guo, Xianni; Wang, Anwei; Wang, Xiuhong; Liu, Jinming; Ma, Jing; et al. (Frontiers in Nutrition, 2023)
Hypertension is a major public health concern that strongly influences the quality of life of people worldwide. Keshan disease (KD) is an endemic cardiomyopathy related to low selenium, threatening residents in rural areas of 16 provinces in China. Furthermore, the prevalence of hypertension in the KD-endemic areas has been increasing annually. However, hypertension research associated with KD has only focused on endemic regions, and no studies have compared hypertension prevalence between endemic and non-endemic areas. Therefore, this study investigated the prevalence of hypertension to provide a basis for preventing and controlling hypertension in the KD-endemic areas, even in rural areas. We extracted blood pressure information from cardiomyopathy investigation data from a cross-sectional study of the KD-endemic and non-endemic areas. The hypertension prevalence between the two groups was compared using the Chi-square test or Fisher’s exact test. Additionally, Pearson’s correlation coefficient was employed to evaluate the relationship between the per capita gross domestic product (GDP) and hypertension prevalence. There was a statistically significant increase of hypertension prevalence in the KD-endemic areas (22.79%, 95% confidence interval [CI]: 22.30–23.27%) over the non-endemic areas (21.55%, 95% CI: 21.09–22.02%). In the KD-endemic areas, more men had hypertension than women (23.90% vs. 21.65%, P < 0.001). Furthermore, the hypertension prevalence was higher in the north than in the south in the KD-endemic areas (27.52% vs. 18.76%, P < 0.001), non-endemic areas (24.86% vs. 18.66%, P < 0.001), and overall (26.17% vs. 18.68%, P < 0.001). Finally, the prevalence of hypertension positively correlated with per capita GDP at province level. In conclusion, the increasing hypertension prevalence is a public health problem in the KD-endemic areas. Healthy diets, such as high consumption of vegetables and seafoods, and foods that are rich in selenium, might help prevent and treat hypertension in the KD-endemic areas and other rural areas in China.